2021
DOI: 10.3389/fpsyg.2021.611788
|View full text |Cite
|
Sign up to set email alerts
|

Humor in Times of COVID-19 in Spain: Viewing Coronavirus Through Memes Disseminated via WhatsApp

Abstract: The COVID-19 crisis, and its ensuing periods of confinement, has generated high levels of social stress on a global scale. In Spain, citizens were isolated in their homes and were not able to interact physically with family members, friends or co-workers. Different resources were employed to face this new stressful and unexpected situation (fitness, reading, painting, meditation, mindfulness, dancing, listening to music, playing instruments, cooking, etc.). Humor was one of the most frequent and widely used st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…In this systematic review, the majority of the studies (64 per cent) aimed to examine the message, i.e., the humorous post, focusing on the tools of humour employed in these posts (Dynel 2020(Dynel , 2022Khan et al 2020 2021) attempted to consider the following elements: source, i.e., the sender (author/sharer), the message, i.e., humorous post, and the receiver, i.e., social media users, in their studies. In some of the studies (12 per cent), two of these elements, i.e., the source and the message, were considered (Abidin 2020;Cancelas-Ouviña 2021;Inyabri et al 2021;Roig & Martorell 2021;Aronson & Jaffal 2022); whereas, in some (10 per cent), the message and the receiver were considered (Hussein & Aljamili 2020;Glǎveanu & de Saint Laurent 2021;Raj & Jayaprakash 2021;Chibuwe & Munoriyarwa 2022). However, none of the studies came up with any comprehensive and focused findings on the cumulative process of communication involving all aspects, viz.…”
Section: Elements Of Communicationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this systematic review, the majority of the studies (64 per cent) aimed to examine the message, i.e., the humorous post, focusing on the tools of humour employed in these posts (Dynel 2020(Dynel , 2022Khan et al 2020 2021) attempted to consider the following elements: source, i.e., the sender (author/sharer), the message, i.e., humorous post, and the receiver, i.e., social media users, in their studies. In some of the studies (12 per cent), two of these elements, i.e., the source and the message, were considered (Abidin 2020;Cancelas-Ouviña 2021;Inyabri et al 2021;Roig & Martorell 2021;Aronson & Jaffal 2022); whereas, in some (10 per cent), the message and the receiver were considered (Hussein & Aljamili 2020;Glǎveanu & de Saint Laurent 2021;Raj & Jayaprakash 2021;Chibuwe & Munoriyarwa 2022). However, none of the studies came up with any comprehensive and focused findings on the cumulative process of communication involving all aspects, viz.…”
Section: Elements Of Communicationmentioning
confidence: 99%
“…The researchers found that intertextuality played a significant role in the structure of humorous posts (Cancelas-Ouviña 2021;Chłopicki & Brzozowska 2021;El-Shokrofy 2021). In the context of Poland, Chłopicki & Brzozowska (2021) argued that the memes illustrated the clash between the world of COVID-19 with that of either the time of the socialist regime that ruled in Poland between 1945 and 1989 or the fictional worlds of films (mainly comedies) produced in the 1970s, 1980s and 1990s, which expressed contempt for the world of socialism.…”
Section: Characteristics Of the Humorous Postsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, I will examine Covid-19 pandemic-related linguistic landscape texts from Latvian cities (hereinafter LL texts), which are published on the internet (news portals; thematic groups of social networks, e.g., Facebook group "Skatlogu favorīti", Favorites of Window-case; and blogs), as well as articles, posts, and readers' responses to them (e.g., reactions, emoticons, written comments, memes, and moving gifs). I will use qualitative methods and content-based theories in data analysis: (1) the social semiotic approach (e.g., Randviir & Cobley, 2010;Kress, 2010), ( 2) critical discourse analysis (e.g., Wodak, 2009;van Dijk, 2015), and (3) humor and creativity theories on digital texts (e.g., Martin, 2007;Cancelas-Ouviña, 2021).…”
Section: Silence and Laughing Through Tears During The Covid-19 Pandemic: Managing Languages And Emotions In Web-based Linguistic Landscamentioning
confidence: 99%